IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA SURABAYA NOMOR 58 TAHUN 2019 TENTANG TATA CARA PENGUMPULAN, PENGOLAHAN, PEMANFAATAN, DAN PELAPORAN DATA MASYARAKAT BERPENGHASILAN RENDAH - Herlambang Bagus Pangarsa (Faculty of Social and Political Science, 2021)
This research uses the theory from Lester and Stewart to determine the implementation of the policy, while determining the factors that influence the implementation of the policy uses four indicators of the implementation policies from Van Meter and Van Horn. The results obtained from the study show that the implementation of the policy is successfully implemented. The factors that affect the whole can be considered well-maintained, although in terms of communication there are several shortcomings, namely the lack of socialization to the community, as well as in terms of resources, especially infrastructure, namely the website application is still error or slow. The tendency factor for implementing the policy has been implemented well because each officer has carried out his functions and duties according to the procedure. The characteristics of the implementing agency are clear, and there is a clear Standard Operating Procedure (SOP) as a guide.